It’s the academia, dummy! or when quantity supersedes quality - Barrera Saldaña, Hugo Alberto (UANL. Facultad de Medicina, 2016)
Many of us, faculty members dedicated to the profession of university professor, began our professional careers investing the best years of our youth in academically preparing ourselves in the best way possible. We continued our careers by searching for a renowned institution to work for. Its prestige provided us with a solid foundation for quick growth, thus reaching the top of the academic hierarchy, making us feel that we made the best investment for our future. Since it is our responsibility to prepare ourselves, it is also our responsibility to make sure this preparation bears the best fruit for society and our families. But also, we aspire to heighten our prestige, even a little, so that at the dusk of our professional life we can feel the satisfaction of having accomplished our mission in society and be rewarded with the appreciation and respect of our colleagues (which results in sincere affection), who we also respect and admire, and fulfill the debt to our family who supported us and sacrificed so much for our eagerness to pursue professional success, a success that has only one noble goal: academic excellence.